A new Data Embedding approach in digital images Using Adaptive Pixel Pair Matching (International Journal of Engineering and Computer Science, 2014)
This paper presents a novel data embedding method using adaptive pixel pair matching (PPM).it is a new Data hiding method which use the value of pixel pair as reference coordinate, and search a coordinate in the neighborhood set of this pixel pair as per the a given message digit. Then the pixel is replaced by the new coordinate to conceal the digit. Exploiting modification direction (EMD) and diamond encoding (DE) are two hiding methods based on PPM. The maximum capacity of EMD is 1.161 bpp. The proposed method offers much lower distortion than DE provides. It allows embedded digits in any notational system by providing compact neighborhood. Comparing with the optimal pixel adjustment process (OPAP) and DE method, the proposed method not only provides better performance but it also has low distortion for various payloads.  It also secure the detection of some well-known steganalysis technique